ANALISIS KIMIA DAUN PINUS DAN PEMANFAATANNYA - Bambang Wiyono; Abdul Hakim Lukman (Jurnal Penelitian Hasil Hutan, 1989)
At   present, pine   needles  have  no  commercial   value.   The  needles  are fire  hazard  to  both  natural  and  plantation grown   trees  when   they  accumulate   on  the  ground,  couple   with  inhibition of  the growth  of  the surrounding   trees.  The research purpose   is to  determine   chemical  component    of pine   needles  of  three  pine  i.e  Pinus  merkusii, P. caribaea, and P. insularis.  This  endeavor  is conducted  to explore  a  wider   of  such  material.The  results  indicated   that  the  moisture   content    of  P. merkusii,   P.  caribaea,   and P.  insularis  needles  were 4.69  %,3.54   %,   and   14.79  %  respectively;   cellulose   content    being   12.31      %,  17.19     %,   and  18.54    %;   lignin  content   29.46%,39.54,   and  26.65   %;  pentosan  content    7.04  %,   5. 78  %,   and   12.11    %;   ash  content   3.06  %,  2.40    %,   and  7.30  %; silica content   0.44  %,  0.48  %,  and 0.19 %; acidity  5.32,  5.33,  and 6.15;   solubility   in cold water 23.38   %, 23.09  %,  and 17.84  %; solubility  in  hot  water  26.51   %,   29.62   %,    and  17.82  %;   solubility   in  alcohol-benzene     (1  :    2)   19.30  %,   19.14  %,  and 11.08  %.  Based  on  this component,  the pine  needles  may  be utilized  as sources  of raw materail for production of glucose, fructose,  ethanol,   ethylene,   pine  needle  oil  for  pharmaceutical   and  perfumery  industries,   etc.  The  needles  can also be used as raw material  for gasification  and anaerobic  fermentation  processes  for  energy  production.